Traditional sexing methods and external egg characteristics combination allow highly accurate early sex determination in an endangered native turkey breed - Salgado Pardo, J. I.; Navas González, Francisco Javier; González Ariza, Antonio; Arando Arbulu, A.; León Jurado, J. M.; Delgado Bermejo, J. V.; Camacho Vallejo, M. E. (Frontiers in Veterinary Science, 2022)
Early sex determination methods are not only crucial in the worldwide massive poultry industry, but also for small-holder producers. The profitability of sexing techniques must be accounted for when aiming to boost management, nutrition, and conservation practices in endangered poultry breeds. This becomes pivotal when the local breed dealt with belongs to an understudied species such as the turkey. So, the main objective of this study is to identify which method combination may report a higher likelihood for successful sex determination in poults across the three pattern varieties of the Andalusian turkey breed. A total of 84 Andalusian turkey poults (42 black, 28 black-roan, and 14 bronze-roan) were evaluated from one to two days old. Sex determination was performed using 15 methods testing external egg metrics and eggshell colour, poult morphological appraisal and phaneroptics, and behavioral traits. Differences across plumage possibilities and for the interaction between sex and plumage were detected when external egg quality was measured. Sex determination through behavioral methods in black-based feathered (black and black roan) male sex individuals showed a sensitivity 7 times higher when compared with the rest of studied individuals (χ2=7.14, df=1, P<0.01). By contrast, for the black-roan plumage females, the method based on down feathers colouring was approximately 4 times more sensitive (χ2=3.95, df=1, P≤0.05). For the bronze-roan pattern, none of the sexing techniques was reported to efficiently predict sex itself. However, the most proper method combination to determine sex, with independence of plumage colour, was physical external egg characteristics, together with down feather colouring and behavioral approaches (‘English method’ and ‘slap technique’). Specificity values were 49.12, 93.33 and 100%, while sensitivity values were 74.64, 91.03 and 100%, which translated into an accuracy of 63.10, 92.26 and 100%, in black, black roan and bronze poults, respectively. Our results suggest that method combination tested in this study could be considered a highly accurate, simple, and affordable alternative for sex determination in turkeys. This could mean a pivotal advance for turkeys’ small-producers as early sex detection can help to plan timely conservational management strategies, which is of prominent importance in the endangered poultry breeds context.